Computed tomography for evaluating right ventricle and pulmonary artery in pediatric tetralogy of Fallot: correlation with post-operative pulmonary regurgitation - Yue Gao (Nature Portfolio, 2018)
Abstract Pulmonary regurgitation (PR) is the most common complication after tetralogy of Fallot (TOF) surgical repair, and long-term PR might result in cardiovascular events. The aim of this study was to assess the influence of pre-operative right ventricle (RV) and pulmonary artery (PA) parameters assessed by dual-source computed tomography on post-operative PR. A total of 41 TOF patients who underwent trans-valve surgical repair were retrospectively recruited. The RV and PA parameters evaluated by pre-operative DSCT were compared between the PR and non-PR groups. Our result revealed that the PA parameters (McGoon ratio, Nakata index, and LPA diameter) and RV parameters (RV length diameter and RV short diameter) all showed significant differences between the two groups (all p < 0.05). There was a significant correlation between PR and LPA diameter (r = 0.361), McGoon ratio (r = 0.413), and Nakata index (r = 0.482). Receiver operating characteristic analysis also revealed a moderate sensitivity and specificity of LPA (66.33%; 82.60%), McGoon ratio (83.33%, 56.52%), and Nakata index (83.33%; 60.87%) for predicting the occurrence of PR. This study indicated that these pre-operative indices calculated by DSCT are associated with post-operative PR and that these pre-operative PA and RV parameters may serve as novel predictors of the risk of PR.